The Association between Energy Cost of Walking and Physical Function in Older Adults - Wert, David M. (2013)
To assess the association between energy cost of walking and self-report of function, independent of comorbidity and gait speed, in older adults with mobility limitations. This cross-sectional observational study was conducted within an ambulatory clinical research training center. Forty-two older adults, age 65 and older, with slow and variable gait participated. Function was assessed using the Late Life Function and Disability Index- Basic Lower Extremity subscale, while energy cost of walking was derived by standardizing the mean oxygen consumption recorded during physiological steady state by gait speed. Comorbidity and gait speed were collected as co-variates. Pearson’s r correlation coefficient and regression analyses were used to assess the relationship between energy cost and function. Energy cost of walking was significantly correlated with self-reported function (Pearson’s r= −.50, p <.001); furthermore, energy cost of walking explained an additional 17% (p=.002) of the variance in self-reported function above and beyond the variance explained by comorbidity and gait speed combined. Energy cost of walking is emerging as another significant factor related to functional performance among older adults, even after controlling for comorbidity and gait speed- robust variables known for their strong contributions to function. Knowledge of and attention to the efficiency of how one moves (high energy cost of walking) may enhance rehabilitation efforts to further reduce “functional burden” in older adults.